Analisis Tindak Tutur Direktif dalam Video Pembelajaran Kurikulum Merdeka pada Channel Youtube Inspirasi Guru - Alya Luthfi Ghani; Azhar Aji Winanda; Dina Handayani Safila Putri; Indri Triani; Mesya Viola Dwi Cahyani; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Didi Pramono (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Speech acts must be done by everyone in everyday life. Speech act must be adjusted to the context of speech. It is expected that speakers understand various types of speech acts. This article aims to study directive speech acts in independent curriculum learning videos on the Inspirasi Guru Youtube channel in order to add insight and providing resources for researchers and readers. This research is conducted so that writers and readers can convey speech properly and correctly according to the context of speech. This research uses a pragmatic approach and analyzes by identifying speech acts, especially directive speech acts in independent curriculum learning videos contained in the Inspirasi Guru Youtube channel. The data information taken is a video that contains types of directive speech acts in independent curriculum learning. This research is using qualitative descriptive methods and pragmatic methods. The data collection technique uses listening and recording techniques. After the research in the learning video of the independent curriculum on the Inspirasi Guru youtube channel, it was found that there were various types of directive speech acts including directive speech acts of inviting, asking, ordering, charging, urging, suggesting, commanding, giving signals, forcing. The results of the analysis of this article are expected to add insight and can be a reference material for analyzing speech acts, especially directive speech acts, it is also expected that writers and readers able to speech in all situations boldly, well, and of course correctly.